NETRALITAS BIROKRASI DALAM PENGAWASAN KEBIJAKAN DAERAH: STUDI PERAN DIREKTORAT JENDERAL OTONOMI DAERAH - Rizka Luluatul Hasanah; Raissa Kevin Ivansyach; Andrew Raymond Jonathan; Shalwa Azahra; Muhammad Prakoso Aji (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Post-1998 reforms in Indonesia have strengthened decentralization and regional autonomy, yet significant challenges remain, including fiscal dependency, limited human resource capacity, and political intervention in regional governance. These conditions require effective supervision by the central government to ensure policy consistency and bureaucratic professionalism. This study analyzes the role of the Directorate General of Regional Autonomy in supervising regional policies and promoting bureaucratic neutrality. A qualitative approach was employed through literature review, interviews, and document analysis. The findings indicate that the Directorate General performs a strategic function by providing guidance, monitoring policy implementation, and evaluating regional government performance. However, its effectiveness is constrained by institutional capacity, coordination issues, and political influence. Bureaucratic neutrality is therefore essential to maintain objectivity, accountability, and professionalism in policy supervision, while strengthening governance quality and supporting effective implementation of regional autonomy across Indonesia.